New Spaces for Climate Change The Societal Construction of Landscapes in Times of a Changing Climate - Köpsel, Vera.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
Vera Köpsel investigates the relevance of local perceptions of landscape and nature for the current topic of adaptation to climate change. She highlights the influence that differing conceptualisations of landscape among actors in environmental management have on their perspectives on climate change and adaptation. Qualitative empirical data from Cornwall (UK) constitutes a valuable foundation for an enhanced theoretical understanding of societal constructions of landscape and their implications for local negotiation processes. Using the example of coastal erosion, the author discusses how contrasting perceptions of a local landscape can significantly complicate consensus‐finding around physical‐material adaptation measures. Contents Climate Adaptation, People-Place Relationships, and Local Actors: Reviewing the Literature The Societal Construction of Landscapes in the Context of Climate Change Adaptation Landscape Narratives in Cornwall and their Implications for Climate Change Adaptation Coastal Erosion at Godrevy - Adaptation in the Context of Local Debates Target Groups Researchers, academics, and scholars in the fields of human and integrative geography, and (constructivist) landscape research Practitioners and decision‐makers in the fields of landscape planning and (environmental) management The Author Vera Köpsel conducted her PhD at the Institute of Geography, University of Hamburg. She now works as a human geographer focusing on human‐environment interactions, stakeholder dialogue and communication at the university's Institute of Marine Ecosystem and Fishery Science.
Climate Adaptation, People-Place Relationships, and Local Actors: Reviewing the Literature -- The Societal Construction of Landscapes in the Context of Climate Change Adaptation -- Landscape Narratives in Cornwall and their Implications for Climate Change Adaptation -- Coastal Erosion at Godrevy - Adaptation in the Context of Local Debates.
Keywords: Human geography; Social sciences -- Philosophy; Environmental sciences -- Social aspects; Human Geography; Social Theory; Environmental Social Sciences